Epstein-Barr Virus and multiple sclerosis in a Spanish cohort: A two-years longitudinal study - Domínguez-Mozo, María Inmaculada; López-Lozano, Lorena; Pérez-Pérez, Silvia; García-Martínez, Ángel; Torrejón, María José; Arroyo, Rafael; Álvarez-Lafuente, Roberto (Frontiers in Immunology, 2022)
OBJECTIVES 1. To analyze the prevalence and levels of anti-EBNA-1 and anti-VCA IgG antibodies of Epstein-Barr virus (EBV) in a Spanish cohort of multiple sclerosis (MS) patients and their interactions with other environmental and genetic risk factors. 2. To analyze the association of the evolution of these antibodies with the clinical response to different disease modifying therapies (DMTs) after two-years of follow-up. 3. To assess their possible correlation with the class II HLA alleles as well as with several SNPs identified in GWAS related to disease susceptibility. METHODS We recruited 325 MS patients without DMT (serum samples were collected 1-3 months before starting a therapy) and 295 healthy controls (HC). For each patient we also collected serum samples 6, 12, 18 and 24 months after starting the DMT. EBNA-1 and VCA IgG titers were analyzed by ELISA; 25(OH)D levels were analyzed by immunoassay; HLA DRB1*15:01 allelic variant was analyzed by Taqman technology. RESULTS 1. 97.8% (318/325) vs. 87.1% (257/295) positives for EBNA-1 in MS patients and HC, respectively (p<0.0001; O.R.=6.7); 99.7% (324/325) vs. 94.6% (279/295) for VCA in MS patients and HC, respectively (p=0.0001; O.R.=18.6). All MS patients were positive for EBNA-1 and/or VCA IgG antibodies vs. 280/295 (94.9%) HC (p<0.0001). IgG titers were also significantly higher in MS patients than in HC. 2. We did not find any statistical correlation in the variation of the EBNA-1 and VCA IgG titers between baseline and 24 month visits with the number of relapses, progression, clinical response, NEDA-3 condition or therapeutic failure. 3. When we compared different epidemiological and clinical variables between those with genetic factors associated with lower EBNA-1 IgG titers and all other MS patients, we found MS started 3.5 years later among the first. CONCLUSIONS These results confirm that MS occurs rarely in absence of EBV. An intriguing association between genetic burden and lower EBNA-1 IgG titters was associated with an earlier age of disease onset. Similar studies with B-cell–targeted therapies should be performed.